2021
DOI: 10.1002/lary.30004
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy‐Based Frequency Allocation in Cochlear Implantation: The Importance of Cochlear Coverage

Abstract: Objectives/hypothesis This study aimed to compare the predicted anatomy‐based frequency allocation of cochlear implant electrodes with the default standard frequencies. Study Design Retrospective study. Methods A retrospective analysis was performed using computed tomography (CT) images of patients who received cochlear implants at a tertiary referral center. Patients were excluded if they had any congenital or acquired cochlear anatomical anomalies. The CT images of the patients were uploaded to the surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…There is evidence for a positive correlation between an AID range within 630°to 720°(corresponding to a CC of 70% to 80%) and the postoperative speech perception (10,11,22). This effect is assumed to be related to a good match between the tonotopy of the cochlea and electrical stimulation by the CI electrode array (2,4,(6)(7)(8)(9)(23)(24)(25)(26)(27). Because the shape and size of the cochlea is unique in every CI recipient, patient-specific electrode array length selection is recommended to achieve the targeted AID range (3,6,10,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence for a positive correlation between an AID range within 630°to 720°(corresponding to a CC of 70% to 80%) and the postoperative speech perception (10,11,22). This effect is assumed to be related to a good match between the tonotopy of the cochlea and electrical stimulation by the CI electrode array (2,4,(6)(7)(8)(9)(23)(24)(25)(26)(27). Because the shape and size of the cochlea is unique in every CI recipient, patient-specific electrode array length selection is recommended to achieve the targeted AID range (3,6,10,21).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is assumed to be related to a good match between the tonotopy of the cochlea and electrical stimulation by the CI electrode array (2,4,(6)(7)(8)(9)(23)(24)(25)(26)(27). Because the shape and size of the cochlea is unique in every CI recipient, patient-specific electrode array length selection is recommended to achieve the targeted AID range (3,6,10,21). Consequently, when using the approach of an individualized CC, an accurate prediction of AID before CI surgery is needed (4,7,9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7] Reduced AID may reduce the frequency stimulation range and increase place-pitch mismatch within the cochlea. [8][9][10][11] However, there has been controversy regarding the ability to achieve high AID without causing scalar translocation, which has been associated with poor hearing outcomes and preservation. 9,12,13 Currently, the highest AID is achieved with 31.5 mm lateral wall electrodes which generally reach between 584 4 and 628 14 on average; however, some studies have found insertion depths past 720 .…”
Section: Introductionmentioning
confidence: 99%
“…The main factor that creates the significant place-pitch differences is the position of the electrode array, which can be determined using high-resolution computed tomographic (CT) imaging and surgical planning software (3). Most publications thus far have retrospectively analyzed 1) the electrode-array insertion depth and place-frequency mismatch as a function of the array length, and 2) the correlation between mismatch and postoperative outcomes (1,(4)(5)(6). Therefore, because of these discrepancies mentioned within the previous literature, there is a need for a new fitting procedure to actively reduce the frequency to place mismatch.…”
Section: Introductionmentioning
confidence: 99%